Increasing knowledge in IGF1R defects: lessons from 35 new patients. Issue 3 (5th October 2019) - Giabicani, Eloïse; Willems, Marjolaine; Steunou, Virginie; Chantot-Bastaraud, Sandra; Thibaud, Nathalie; Abi Habib, Walid; Azzi, Salah; Lam, Bich; Bérard, Laurence; Bony-Trifunovic, Hélène; Brachet, Cécile; Brischoux-Boucher, Elise; et al.
Abstract : Background: The type 1 insulin-like growth factor receptor (IGF1R) is a keystone of fetal growth regulation by mediating the effects of IGF-I and IGF-II. Recently, a cohort of patients carrying an IGF1R defect was described, from which a clinical score was established for diagnosis. We assessed this score in a large cohort of patients with identified IGF1R defects, as no external validation was available. Furthermore, we aimed to develop a functional test to allow the classification of variants of unknown significance (VUS) in vitro. Methods: DNA was tested for either deletions or single nucleotide variant (SNV) and the phosphorylation of downstream pathways studied after stimulation with IGF-I by western blot analysis of fibroblast of nine patients. Results: We detected 21 IGF1R defects in 35 patients, including 8 deletions and 10 heterozygous, 1 homozygous and 1 compound-heterozygous SNVs. The main clinical characteristics of these patients were being born small for gestational age (90.9%), short stature (88.2%) and microcephaly (74.1%). Feeding difficulties and varying degrees of developmental delay were highly prevalent (54.5%). There were no differences in phenotypes between patients with deletions and SNVs of IGF1R . Functional studies showed that the SNVs tested were associated with decreased AKT phosphorylation. Conclusion: We report eight new pathogenic variants of IGF1R and an original case with a homozygous SNV. We found the recently proposed clinical score to be accurate for the diagnosis of IGF1R defects with a sensitivity of 95.2%. We developed an efficient functional test to assess the pathogenicity of SNVs, which is useful, especially for VUS.